Re-examination of MAGE-A3 as a T-cell Therapeutic Target. Issue 3 (April 2021) - Martin, Aaron D.; Wang, Xueyin; Sandberg, Mark L.; Negri, Kathleen R.; Wu, Ming L.; Toledo Warshaviak, Dora; Gabrelow, Grant B.; McElvain, Michele E.; Lee, Bella; Daris, Mark E.; Xu, Han; Kamb, Alexander
Abstract : In 2013, an innovative MAGE-A3-directed cancer therapeutic of great potential value was terminated in the clinic because of neurotoxicity. The safety problems were hypothesized to originate from off-target T-cell receptor activity against a closely related MAGE-A12 peptide. A combination of published and new data led us to test this hypothesis with current technology. Our results call into question MAGE-A12 as the source of the neurotoxicity. Rather, the data imply that an alternative related peptide from EPS8L2 may be responsible. Given the qualities of MAGE-A3 as an onco-testis antigen widely expressed in tumors and largely absent from normal adult tissues, these findings suggest that MAGE-A3 may deserve further consideration as a cancer target. As a step in this direction, the authors isolated 2 MAGE-A3 peptide-major histocompatibility complex-directed chimeric antigen receptors, 1 targeting the same peptide as the clinical T-cell receptor. Both chimeric antigen receptors have improved selectivity over the EPS8L2 peptide that represents a significant risk for MAGE-A3-targeted therapeutics, showing that there may be other options for MAGE-A3 cell therapy. Abstract : Supplemental Digital Content is available in the text.